RESPONSE OF YOUTUBE SPECTATORS TO INTEGRATED PROPAGANDA TO THE VIDEO CONTENT - Corso, Kathiane Benedetti (2019)
This article purpose to analyze the response of YouTube users to advertisement inserted within the content of videos. To reach this aim, an exploratory and qualitative research was carried out through the netnographic method. As main results it was perceived that there are five models used by content producers for the insertion of advertisements in the content of videos. The models with the highest response from users were those who presented the product for a longer period of time. Since the advertisements that presented a more positive response from the users were those that generated information, entertainment or were customized for the audience that attended them.